Senior Women's Leadership: A Case Study in the Social Organization of the Association of Veteran Wives of the Republic of Indonesia (PIVERI) - Indiarti, Indiarti; Lina, Lina (Journal of Economics and Business UBS, 2025)
This study aims to explore the dynamics and characteristics of senior female leadership within the social organization of the Persatuan Istri Veteran Republik Indonesia (PIVERI), particularly at the Regional Management level. PIVERI is a women-based organization comprised of the wives of veterans, with members ranging in age from 50 to 90 years, who continue to play an active role in advancing the independence of Indonesian women. Employing servant leadership and transformational leadership frameworks, this research utilizes a qualitative approach with a multiple case study design. Data were collected through in-depth interviews and participatory observation of seven PIVERI Regional Management Boards across various regions of Indonesia. The interview results revealed that in six Regional Management Boards with strong performance, the application of servant leadership was evident, particularly in elements such as persuasion, awareness, community building, listening, and empathy, which appeared consistently and significantly. The leadership competencies of senior women in PIVERI are supported by extensive experience, diverse educational backgrounds, and advanced organizational skills. Their leadership characteristics reflect collaborative values, emotional maturity, and a strong commitment to the organization’s social mission. This research underscores the importance of establishing leadership age limits, providing education for members of productive age, and securing government support to strengthen the role of senior women-based social organizations. These findings contribute to the broader study of women’s leadership in the context of social organizations and offer practical implications for enhancing similar organizational structures and leadership strategies in the future.